"A lo lejos" – Aging in place and transnational care in the case of transnational migration between Cuba and Germany. Issue 1 (2nd January 2017) - Brandhorst, Rosa María
Abstract: This article analyzes family care and aging in place in transnational families between Cuba and Germany. It draws on the results of a longitudinal multi-sited research on transnational families, based on reconstructive analysis of participant observations and biographical-narrative interviews with Cuban migrants in Germany and their relatives in Cuba. Adopting a case level of family histories enables me to see how the exchange of care is negotiated across generations. In this article, two case studies will provide a detailed description of transnational care and aging between Cuba and Germany. Originating from a transnational migration studies background, this article addresses the implications of the transnationalization of life worlds and the possibility to maintain contact via information and communication technologies for the concept of aging in place. Furthermore, it discusses the influence of structural constraints (like restrictions of travel and ICTs access) on aging in a transnational place. The restrictions in the Cuban case highlight the impediments of transnational caregiving through national migration, healthcare, and other policies. Immediate communication through ICTs cannot be generalized. Thus, this article explores the importance of an imagined sense of belonging to a transnational family as an emotional resource for aging in a transnational place.